Prevalence of no harm incidents and adverse events in a surgical clinic - Thatianny Tanferri de Brito Paranaguá (Acta Paulista de Enfermagem, 2013)
Objective: To estimate the prevalence of no harm incidents and adverse events in a surgical clinic. Methods: Cross-sectional study conducted with a sample of 750 hospitalizations in the surgical clinic of a hospital in the mid-west region. A descriptive analysis was performed and the prevalence of incidents was calculated. Results: It was demonstrated that 615 hospitalizations were exposed to no harm incidents and 140 to adverse events. Of the 5,672 reported incidents, 218 were characterized as adverse events that caused harm to the patient. No harm was proven for the others; however, they highlighted the need for an adjustment to work processes. Conclusion: The prevalence of no harm incidents was estimated at 82%, and 18.7% for adverse events.